Epidemiological evidence of carcinogenicity of sunbed use and of efficacy of preventive measures. (27th February 2019) - Gandini, S.; Doré, J.‐F.; Autier, P.; Greinert, R.; Boniol, M.
Abstract: The International Agency for Research on Cancer classified, in July 2009, exposure to artificial tanning devices (sunbeds) as carcinogenic to humans. This classification was based on evidence from epidemiological and experimental animal studies. The present chapter will review these epidemiological evidences. The summary risk estimates from 27 epidemiological studies obtained through a meta‐analysis showed an increased risk of melanoma: summary relative risk (SRR) = 1.20 [95% confidence interval (CI) 1.08–1.34]. The risk was higher when exposure took place at younger age (SRR = 1.59; 95% CI 1.36–1.85). The risk was independent of skin sensitivity or population and a dose response was evident. A meta‐analysis of 12 studies was conducted for non‐melanoma skin cancers and showed a significantly increased risk for basal cell carcinoma (SRR = 1.29; 95% CI 1.08–1.53) and for squamous cell carcinoma (SRR = 1.67; 95% CI 1.29–2.17). As for melanoma, the risk for other skin cancers increased for first exposures at young age. Epidemiological studies have gradually strengthened the evidence for a causal relationship between indoor tanning and skin cancer and they fit with prior knowledge on relationship between UV exposure and skin cancer. Additionally, several case–control studies provided consistent evidence of a positive association between use of sunbed and ocular melanoma, also with greater risk for first exposures at younger age. Preventive measures based on information on risk or by requiring parental authorization for young users proved to be inefficient in several studies. The significant impact of strong actions or total ban, such as performed in Iceland, or a total ban of sunbed use, as in Brazil or Australian states, needs to be further assessed.